The Effect of Citrus Aurantium Vaginal Cream on Vaginal Atrophy in Postmenopausal Women: A Quasi-experimental Study - Homeira Asgharpoor; fatemeh Hadizadeh Talasaz; Roghayeh Rahmani; Hasan Rakhshandeh; Zahra Rahmati (International Journal of Community Based Nursing and Midwifery, 2024)
Background: Vulvovaginal atrophy (VVA) is a common condition and a silent epidemic affectingmany postmenopausal women who suffer from it in silence. This study aimed to evaluate the effect ofCitrus aurantium vaginal cream on vaginal atrophy in postmenopausal women.Methods: This single-group pretest-posttest quasi-experimental study was conducted on 30postmenopausal women who were referred to the Gynecology Clinic of Imam Khomeini Hospital in thecity of Noor, Iran, from June to November 2020. Citrus aurantium vaginal cream was administered towomen diagnosed with vaginal atrophy (based on subjective symptoms of atrophy, descriptive evaluationof the vagina, vaginal pH measurement, and degree of vaginal maturation determined by vaginal smear)every night in the first two weeks and every other night for the second two weeks. Data were collectedusing the scale of subjective symptoms of vaginal atrophy; descriptive evaluation checklist of vaginalmucosa; laboratory results registration form (vaginal maturation index, vaginal maturation value, andvaginal pH) before the intervention and two and four weeks after the intervention. Data were analyzedusing SPSS software (version 24) through the analysis of variance with repeated measurements, andLSD post-hoc test. A P value less than 0.05 (P<0.05) was considered statistically significant.Results: Citrus aurantium vaginal cream improved subjective symptoms of vaginal atrophy (P<0.001),reduced the score of descriptive evaluation of vaginal mucosa (P<0.001), decreased vaginal pH(P<0.001), and increased vaginal maturity (P<0.001).Conclusions: The results showed that citrus aurantium vaginal cream could improve the symptoms ofvaginal atrophy without causing serious complications. However, further studies with a control groupare suggested to confirm the findings of this study.Trial Registration Number: IRCT20200215046494N1